2018
DOI: 10.1172/jci99032
|View full text |Cite
|
Sign up to set email alerts
|

Nano-targeted induction of dual ferroptotic mechanisms eradicates high-risk neuroblastoma

Abstract: High-risk neuroblastoma is a devastating malignancy with very limited therapeutic options. Here, we identify withaferin A (WA) as a natural ferroptosis-inducing agent in neuroblastoma, which acts through a novel double-edged mechanism. WA dose-dependently either activates the nuclear factor-like 2 pathway through targeting of Kelch-like ECH-associated protein 1 (noncanonical ferroptosis induction) or inactivates glutathione peroxidase 4 (canonical ferroptosis induction). Noncanonical ferroptosis induction is c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
440
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 477 publications
(448 citation statements)
references
References 61 publications
(81 reference statements)
7
440
0
1
Order By: Relevance
“…All three treatments altered a common set of 23 genes ( Fig. 3f and Supplementary Table 2) including genes previously identified as increased during ferroptosis including RHOB, SLC2A3, DDIT4 and HMOX1 15,29 . In addition, the previously reported ferroptosis marker CHAC1 29 was commonly upregulated in both tung-oil treated tumors and αESA-treated cells.…”
Section: Conjugated Pufas Exhibit Anti-cancer Activity and Promote Exmentioning
confidence: 93%
See 1 more Smart Citation
“…All three treatments altered a common set of 23 genes ( Fig. 3f and Supplementary Table 2) including genes previously identified as increased during ferroptosis including RHOB, SLC2A3, DDIT4 and HMOX1 15,29 . In addition, the previously reported ferroptosis marker CHAC1 29 was commonly upregulated in both tung-oil treated tumors and αESA-treated cells.…”
Section: Conjugated Pufas Exhibit Anti-cancer Activity and Promote Exmentioning
confidence: 93%
“…
Recent studies have shown that cancer cells, including renal cell carcinoma, melanoma and glioblastoma are vulnerable to ferroptosis [10][11][12][13][14][15][16] . Furthermore therapy-resistant mesenchymal cancer cells exhibit a greater reliance on GPX4 activity for survival 10,17 .
…”
mentioning
confidence: 99%
“…For a detailed description of class I-III FINS refer to Yang et al (240), Dixon and Stockwell (2), and Lu et al (237). Although, it is classed as type II, withaferin A, a natural ferroptosisinducing agent, increases the intracellular iron pool and inhibited growth of neuroblastoma xenografts (241). Likewise, artesunate, an anti-malarial, interacts with lysosomal iron and generates ROS leading to ferroptosis.…”
Section: Ferroptosismentioning
confidence: 99%
“…Ferrostatin-1 distinctly raises the GPX4 and FTH1 expression and blocks the PTGS2 and ACSL4 level [50]. In lung cancer cell lines, cell proliferation is decreased with GPX4 knockdown and this inhibition could be reversed by ferrostatin-1, the speci c inhibitor of ferroptosis [14,51]. These results further indicated that GPX4 can negatively regulate ferroptosis, and ferrostatin-1 partially reversed the effect of sh-GPX4.…”
Section: Discussionmentioning
confidence: 79%